Earnings response coefficient of banking shares: a multi-country study with control for risk - Syed Mohamed, Mohamed Ariff; Cheng, Fan Fah (Universiti Putra Malaysia Press, 2013)
This paper reports new finding on earnings response coefficients of banking firms on how information disclosed regarding (i) total earnings and (ii) fee earnings is associated with share price changes around the time of financial report releases. This paper extends to banking firms a widely used analysis of earnings response studies on non-banking firms. To obtain robust test results, we extended this common model, for the first time, by adding control variables and also by applying panel regression. Changes in total earnings do influence share prices significantly in the four countries studied i.e. Malaysia, Thailand, South Korea and Australia. Australian investors appear to use disclosed information on fee income also to revise share prices significantly as being value relevant. Investors regard both total and fee incomes as equally important in Australia whereas investor actions in the other three markets studied lead to weak evidence on fee income effect. This paper reports new findings on value relevance of disclosures extended to banking firms.